Corporate Social Responsibility (CSR) Sebagai Strategi Hukum Lingkungan Dalam Upaya Mendukung Pembangunan Berkelanjutan - Pangestu, Muhammad Teguh (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2025)
Corporate Social Responsibility (CSR) is present as one of the mechanisms that can bridge economic interests and environmental conservation. CSR is not just a form of corporate generosity to the community, but has developed into a strategic instrument that has legal implications. CSR encourages companies to internalize social and environmental values into their business activities, so that the company's existence is not only profit-oriented, but also contributes to social welfare and environmental sustainability. The methods used in this study are normative juridical, legal research with a doctrinal approach, or normative juridical legal research. Normative law research is basically an activity that will examine aspects to solve problems that exist within the internal of positive law. The implementation of CSR in Indonesia still faces various structural challenges. One of them is weak supervision from the government, lack of transparency in CSR reports, and lack of firm sanctions against companies that do not carry out these obligations. Many companies still carry out CSR in a formality just to meet administrative requirements or improve public image, not as a real commitment to social and environmental sustainability. This is due to the lack of a standard evaluation mechanism and differences in legal interpretations regarding the ideal form and size of social responsibility. In addition, CSR reporting is often out of sync with the principles of transparency and public accountability, making it difficult for the public to assess the extent to which a company's contribution truly provides concrete benefits to the environment and surrounding communities.